Kahkaha terapisinin hemodiyaliz hastaları üzerindeki etkisi : randomize kontrollü çalışma - Eraydın, Canan (My University, 2023)
Amaç: Bu araştırma hemodiyaliz hastalarına uygulanan kahkaha terapisinin; serum kortizol düzeyine, depresyon, anksiyete, stres düzeylerine ve yaşam kalitesi üzerine etkisini incelemek amacıyla ön test, son test kontrol gruplu deneysel tasarım ile yapılmış bir çalışmadır. Gereç ve Yöntem: Araştırma Zonguldak il merkezinde bulunan, iki Diyaliz Merkezinde hemodiyaliz tedavisi gören ve araştırmaya dâhil edilme kriterlerini karşılayan 80 hasta üzerinde Mart 2021- Haziran 2021 tarihleri arasında yürütüldü. Araştırmada Tanıtıcı Özellikler Bilgi Formu, Depresyon Anksiyete ve Stres Ölçeği, Böbrek Hastalığı Yaşam Kalitesi Formu kullanıldı ve kortizol için hastalardan kan örneği alındı. Kahkaha terapisi haftada üç gün olmak üzere, 4 hafta boyunca toplam 12 seans yapıldı. Bulgular: Yaşam kalitesi alt boyutlarından, fiziksel ve mental sağlık durumları, hastalığın günlük yaşam yükü, son testte deney grubunda kontrol grubunda olan hastalara göre daha yüksekti (sırasıyla t=-10.454, p<0,001, t=-4,568, p<0,001). Serum kortizolünün ön test-son test puan ortalamaları istatistiksel olarak anlamlı değildi (p>0,05), fakat her iki gruptaki hastaların ön test-son test kortizol puanları birbirine yakındı (sırasıyla t=1,759, p=0,088, t=-1,853, p=0,072). Son testte ölçülen Anksiyete, Depresyon ve Stres Ölçeği toplam puanları ve alt boyutlarının deney grubunda daha düşük olduğu saptandı (sırasıyla t=5.050, p<0,001, t=7.872, p<0,001, t=6.927, p<0,001, t=8.304, p<0,001). Sonuç: Kahkaha terapisi hemodiyaliz hastalarının serum kortizol düzeylerini etkilememekle birlikte, depresyon, anksiyete ve stres düzeylerini azaltmada, yaşam kalitesini arttırmada etkilidir.

Aim: This study aimed to determine the laughter therapy applied to hemodialysis patients; This is an experimental design with pretest and post-test control groups to examine the effects on serum cortisol levels, depression, anxiety, stress levels, and quality of life. Methods: The study was conducted between March 2021 and June 2021 on 80 patients who were treated with hemodialysis in two Dialysis Centers in Zonguldak city center and met the inclusion criteria. In the study, İntroductory İnformation Form, Depression Anxiety and Stress Scale, and Kidney Disease Quality of Life Form were used and blood samples were taken from the patients for cortisol. Laughter therapy was performed three days a week, for a total of 12 sessions over 4 weeks. Results: Among the sub-dimensions of quality of life, physical and mental health conditions, daily life burden of the disease were higher in the experimental group than in the control group in the post test (t=-10.454, p<0,001, t=-4,568, p<0,001). Pre test-post test mean scores of serum cortisol were not statistically significant (p>0,05), but the pre test-post test cortisol scores of the patients in both groups were close to each other (t=1,759, p=0,088, t=-1,853, p=0,072, respectively). Anxiety, Depression, and Stress Scale total scores and sub-dimensions measured in the post test were found to be lower in the experimental group (t=5,050, p<0,001, t=7,872, p<0,001, t=6,927, p<0,001, t=8,304, respectively, p<0,001). Conclusion: Although laughter therapy does not affect the serum cortisol levels of hemodialysis patients, it is effective in reducing depression, anxiety and stress levels and increasing the quality of life.
Effect of laughter therapy on hemodialysis patients : a randomized controlled study
Keywords: Anksiyete; anksiyeteSerum cortisol; Anxiety; Depression; Depresyon; Hastalar; Hemodialysis; Hemodiyaliz; hemşirelik; nursing; Patients; quality of life; Serum kortizol; Tedavi; Treatment; yaşam kalitesi